PENGARUH TIPE-TIPE STRUKTUR KEPEMILIKAN DAN FAKTOR-FAKTOR FUNDAMENTAL TERHADAP KINERJA BEBERAPA BANK "BERMASALAH" DI INDONESIA: OBSERVASI TAHUN 19914997** - Bahtiar Usman; Ignatius Roni Setyawan (Media Riset Bisnis & Manajemen, 2008)
This research aims to analyze the effect of ownership types & fundamental factors toward bank performance in Indonesian case 1991-1997. The idea is derived from study of Rokhim (2006); which stated that banks with higher related lending will be more fragility. In that study, she identifies several fundamental factors such as Cost of Fund; Size and Net Open Position. Different with Rokhim (2006), we focus to the effect of ownership type toward bank performance. We argue that related lending couki be caused by ownership type. As we know from agency, theory, the more concentrated ownership the higher related lending. Three important findings of our research are as follow: 1) Ownership Type and Fundamental Factors have significant effect toward bank performance. It implies to support indirectly study of Rokhim (2006). 2) From eight variables of ownership type only family; foreign, Soeharto, Listed and Cross and three variables of Fundamental Factors, only cost respectively have a significant effect in level 5 % toward bank performance unless family. 3) Robustness test with GLS fixed effect has consistent result with OLS non data panel.Key words: bank performance; ownership type; fundamental factors